Low-cost poly(vinyl formal) for heavy metal removal from water of a polluted river. Issue 1 (15th February 2022) - Villanueva-Flores, Francisca; Palomares, Laura A.
Abstract: Heavy metal pollution in drinking water is a serious health risk, particularly in developing countries. Membranes of poly(vinyl formal) (PFA) were synthesized to explore their use for heavy metal removal from water samples from the polluted Mexican river 'Atoyac.' A single incubation step with PFA membranes for 24 h was sufficient to reduce lead, iron, manganese, arsenic, and thallium concentrations to acceptable levels for drinking water, according to the Mexican standards. PFA showed high adsorption capacities ( Qe ), even in the presence of multiple metals and low cation concentration. Mass transport phenomena were characterized as a function of the crosslinking degree and pH. To simulate real-life operation conditions, water fluxes across PFA membranes were characterized as a function of their crosslinking degrees and controlled external pressures. PFA membranes allowed fluxes at pressures of up to 2 kg/cm 2 with no deformation or breaking. Tensile strength, strain stress, elastic deformation, and Young's modulus were assessed. In contrast with previous reports, no further PFA modifications were required to obtain an excellent adsorption performance, which results in lower production costs. The ease of PFA synthesis and handling, and low production cost make it an ideal material to be applied for remediating the polluted urban water. HIGHLIGHTS: PFA membranes can efficiently adsorb hazardous cations from complex water samples. Material properties could be easily modulated to obtain a desired adsorption capacity. PFA has good mechanical and chemical resistance. PFA is easily synthesized and handled, has a very low cost, and is an ideal candidate material for remediating the polluted urban water.